Penguatan Kewenangan DPD Dalam Sistem Ketatanegaraan Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 92/PUU-X/2012 - Abdul Hakim Siagian (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
In a federal state, the system of representation of its people is divided into rooms (cameral). In the room division system, the DPR and DPD have a system commonly called checks and balances. Each of the chambers supervises and matches each other's performance, in the sense that the DPD should have the same authority as the DPR in the legislative function. This study aims to describe the authority of the DPD and optimize the role of the DPD in the legislative function after the Constitutional Court Ruling Number 92 / PUU-X / 2012. This research is a normative research sourced from books and documents about DPD. The results of this study indicate that the DPD's authority is weak because it is still considered as a co-legislator of the DPR and the form of its optimization can be done through the fifth amendment or the renewal of the Law forming legislation and the MD3 Law. Then the weakness of the DPD which results in a weak system of checks and balances in the parliament must be optimized DPD authority.